PSYCHOCORRECTION AND PSYCHOPROPHYLAXIS OF DEVIATIONS, TAKING INTO ACCOUNT THE PECULIARITIES OF PROTECTIVE AND COPING BEHAVIOR OF ADOLESCENTS - Kalillayeva Ulbosin Ayapbergenovna (Scholar Express Journal, 2022)
The article raises the problem of an approach to the study and psychocorrection of deviant behavior from the standpoint of effectivenessinefficiency of protective and coping behavior. the urgency of the raised problem is due to a number of circumstances: a steady increase in crime in general and juvenile delinquency in particular, difficulties in choosing methods of education and influencing adolescents who exhibit behavioral deviations. The protective and coping behavior of minors is considered as one of the levels of socio-psychological adaptation, the essential role of the system of psychological protection and coping in the formation of deviant behavior is emphasized. The question is raised about the expediency of carrying out effective measures for the prevention and prevention of juvenile delinquency, psychocorrection based on the diagnosis of the functioning of the protective coping system, the specifics of the available coping resources in order to form productive coping strategies, reduce the protective activity of adolescents.
Keywords: Deviant Behavior; Psychological Defense; Coping Strategies; Coping Resources